Interactions Between Cyclodextrins and TmIII Chelates of Polyazamacrocycles as Studied by NMR in Aqueous Solution - Zitha-Bovens, Emrin (1999)
The interactions between α-, β-, and γ-CD and the TmIII chelates of the macrocyclic polyaminopolycarboxylates DOTA and NOTA were studied with the use of 1H- and 13C-NMR shift and relaxation rate measurements. Interactions were only observed between Tm(DOTA)- and γ-CD. The structure and the stability of the concerning supramolecular structures was elucidated by fitting of the NMR titration curves to a theoretical model. It appears that an inclusion compound is formed, where the hydrophobic macrocyclic part of the chelate sits in the γ-CD cavity. This inclusion compound binds a second Tm(DOTA)- molecule at the outside lower rim of the CD cone. The binding occurs probably via hydrogen bonds between non-chelated carboxylate oxygen atoms of the concerning Tm(DOTA)- and CH2OH groups of the γ-CD molecule, which are in a favorable position due to opening of the γ-CD cone angle as a result of the inclusion of the first γ-CD.